Synthesis, characterization, and thermal behavior of 4-chloromethyl-2-(2-hydroxynaphthylidenehydrazino) thiazole and its complexes with Cr(III), Co(II), Ni(II), and Cu(II) - Saydam, S; Yilmaz, E (Taylor & Francis Inc, 2005)
A new ligand, 4-chloromethyl-2-(2-hydroxynaphthylidenehydrazino) thiazole, has been synthesized from dichloroacetone and 2-hydroxynaphthylidenethiosemicarbazone. Metal complexes of the ligand were prepared from acetate salts of Co(II), Cu(II), Ni(II), and chloride of Cr(III) in dry acetone. Characterization of the ligand and its complexes were made by microanalyses, FT-IR, (13)C, (1)H NMR, and UV-Visible spectroscopy, magnetic susceptibility, thermogravimetric analysis. In the light of these results it was suggested that two ligands coordinate to each metal atom by hydroxyl oxygen, imino nitrogen and thiazole ring nitrogen to form high spin octahedral complexes with Cr(III), Co(II), Ni(II), and Cu(II).
Keywords: 4-chloromethylthiazole; 2-hydroxynaphthylidenehydrazine; 4-chlormethyl-2-(2-hydroxynaphthilidenehydrazino) thiazole; Cr(II); Co(II); Ni(II); Cu(II); complex